Scottish women's suffrage movement, 1902-1933. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2014)
The Glasgow and West of Scotland Society for Women's Suffrage was a non-militant suffrage society. Their work continued after that of the many militant societies who ceased campaigning in 1918. With close ties to the Scottish Council for Women's Trades, these women were of a certain social class. They attracted a number of Liberal Lord Provosts and Town Councillors, as well as MPs. The Society's emphasis was upon fundraising, this usually involved flag days and whist drives. When the Society was wound-down in 1933, it was due to a lack of funds and former members would meet at the Queen Margaret Union in the University until the 1960s.
Date range: 1902-1933.
Keywords: Women -- Suffrage -- Scotland; Suffragists -- Scotland